Detection of Bartonella spp. in a Pipistrellus Pipistrellus Bat from Portugal - Gonçalo Barros; Sara Gomes-Gonçalves; Luísa Rodrigues; Carlos Carrapato; Gabriela Fernandes Silva; Irina Amorim; João Rodrigo Mesquita (Veterinary Sciences)
In recent years, zoonotic pathogens have become increasingly more relevant in scientific research due to their implications on public health. Understanding their pathogenic potential, the pathways they use to infect and their reservoirs enables better care for both human and animal patients, and possible infection outbreaks can be more easily contained. Bartonella belongs to a vast list of zoonotic pathogens that can infect mammals, including humans, but also companion animals and wildlife, and is capable of causing disease. Bats are a possible source and reservoir of this bacterial genus, and Bartonella spp. has already been identified in these animals in several countries. Using these premises, skin samples of the pinna and wing of 71 bats (Pipistrellus pipistrellus) collected from southern Portugal were tested through PCR for the presence of Bartonella spp., and positive results were found in 1.41% (1/71). The sequence obtained shared genetic proximity with an already known pathogenic Bartonella strain that affects both humans and animals. From the public health perspective, these findings suggest that bats may play a role in the transmission of this pathogen and provides new insights into the presence of this agent in Portugal.